Do Oxygen Isotope Values in Collagen Reflect the Ecology and Physiology of Neotropical Mammals? - Crowley, Brooke E.; Melin, Amanda D.; Yeakel, Justin D.; Dominy, Nathaniel J. (Frontiers in Ecology and Evolution, 2015)
Stable isotope data provide insight into the foraging ecology of animals. Traditionally, carbon and nitrogen isotope values have been used to infer dietary and habitat preferences. Oxygen isotopes are used less frequently but may complement the ecological information provided by carbon and nitrogen, particularly in densely forested or arid environments. Additionally, because oxygen is preserved in both bioapatite and collagen, it is useful for paleoecological studies. To investigate the suitability of oxygen isotopes for complementing and building on ecological applications of carbon and nitrogen isotopes, we analyze all three isotopes in bone collagen for nearly identical assemblages of Costa Rican mammals in two ecologically distinct habitats - a evergreen rainforest and a seasonal dry forest. We assess the degree to which differences in habitat, activity pattern, diet, arboreality, and thermoregulation are revealed by each of the isotope systems. Our results highlight the potential of oxygen isotopes in modern and paleoecological contexts. In addition to reflecting habitat type, oxygen isotope values in collagen distinguish species on the basis of vertical habitat stratification and drinking behavior. Within a locality, individuals with low oxygen isotope values likely track meteoric water, whereas those with elevated values most likely consume evaporatively-enriched plant tissues, such as canopy leaves. These patterns will be useful in reconstructing paleoenvironments and interpreting ecological differences among taxa both extant and extinct.